Lumpfish physiological response to chronic stress - Lopes, Tiago da Santa; Costas, Benjamin; Ramos-Pinto, Lourenço; Reynolds, Patrick; Imsland, Albert K. D.; Aragão, Cláudia; Fernandes, Jorge M. O. (Frontiers in Marine Science, 2024)
In this study, we explored the effects of chronic stress on lumpfish (Cyclopterus lumpus) physiological, immune response, health, and plasma free amino acids. 3 groups of lumpfish were exposed to 1-minute air exposure. 1 group was exposed to stress once per week, a second group exposed 2 times per week, and a third group exposed 4 times per week. The present study revealed significant alterations in immunity and increased nutritional demands, particularly the branched chain amino acids and lysine. Cortisol levels fluctuated, with significantly higher levels halfway through the experiment on the groups that were stressed more often. Though, by the end of the experiment, there were no significant differences in cortisol levels between groups. Regardless of stress exposure, cataract developed in virtually all sampled fish, pointing toward a potential dietary imbalance. A transient immunomodulation of stress was visible. While in early stages stress had an immune enhancing effect, as seen by the increase in plasma nitric oxide and peroxidase in the group most frequently exposed to stress, these differences were not apparent by the end of the experiment. Additionally, the worst health condition was found in this group. Our results underscore the complex interplay between stress, immunity and nutrition, highlighting the need for tailored dietary strategies and improved rearing practices.